(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
US Department of State’s Offi ce to Monitor and Combat Traffi cking in Persons Annual Report (CTIP, 2008) classifi ed Namibia as a special case on the basis that whereas there was evidence that traffi cking in persons especially for sexual exploitation, was rife, the trend remained largely un-researched and un-documented. This researcher therefore aimed to establish whether human traffi cking as a social and economic activity existed in Namibia, and if so, its prevalence levels, extent, causes and impact and consequences on both its victims and society as a whole, and if so, whether it was targeting prostitutes into the regional and global sex trade industry in particular. The researcher thus gathered and analysed comprehensive quantitative and qualitative data generated through a standardized validated questionnaire to 230 respondent prostitutes representing 191 females and 39 males, and information provided by 18 case studies of real life human traffi cking victims, 32 key informants and 6 Focus Group Discussion meetings (FGDMs) comprising mainly of interest groups in prostitution hot spots in 18 out of 35 regional metropolises and border posts of the country. The study further interrogated the concepts of traffi cking, prostitution and exploitation within the context of its fi ndings, existing social concepts and structures and the day-to-day realities of the lives of individual and groups of people exposed to them. The study results established that while sex traffi cking as a social phenomenon exists in Namibia, it remained largely unknown and understood. Similarly, whereas it was a fairly new phenomenon, it was growing fast, aff ecting mainly unemployed young women, school-drop-out adolescents and orphans, who once they enter the industry, enjoy a symbiotic social and economic relationship with a mobile clientele of mainly tourists and long-distance commercial transporters. They inevitably get exposed to physical and health hazards including physical violence, abandonment, homelessness and diseases, among them Sexually Transmitted Infections (STI) and HIV. The study concluded that prostitution and sex traffi cking in Namibia are social, economic and gender-inequality issues that require urgent attention by relevant authorities and development agencies in terms of prevention and protection interventions at policy, legislative and service levels.